Inclusão digital de alunos de escola da rede pública municipal de ensino: uma visão crítica sobre o processo - Palácio, Patrícia Passos Gonçalves (2006)
The present study gathers several experiences, searches and questionings of the researcher along its professional and academic l1fe. Initjally, it establ1shes the research scenario: Primary School Maria Antonieta D'AlkiminBasto and Anhembi Morumbi University, partners of the project Fim de Semana Digital (Digital Weekend) - whkh main objective was to provide new technologies for information and communication to teachers and students from the Brazllian publk educational system. As following, it is described the related project and its scenario: the project's deploying conditions, the partnership establ1shed with the primary school mentioned above, the pedagogical propose of the initiative, curriculum organization issues and general deployment barriers. In a secondary moment, based on questionnaires analysis, workshops and interviews conducted following a qual1tatlve approach, this dissertation study includes information about established relations, students interests and needs, and also different roles assumed by each individual to what we denominate technologkal culture. The complexity, the level of commitment to this culture, finally, all t~hedimensions involved in the dynamk of the digital inclusion's process were obseried considering the students experiences, focusing the intentional character of the learning along this route. At last, without the intension to offer pre-defined ways, it contributes to the reflection about how, effectively, this practicat experience occurs and also others maygrow up from it